Expression of proenkephalin messenger RNA by mouse spermatogenic cells. - Kilpatrick, D L (1986)
The presence of proenkephalin mRNA in germ cells purified from adult mouse testis were examined using RNA gel- and dot-blot analyses. Both pachytene spermatocytes and round spermatids were shown to contain concentrations of this transcript that are 2- to 3-fold greater than that found for whole mouse testis, on a per microgram of polyadenylylated RNA basis. The detection of proenkephalin mRNA in purified spermatocytes and spermatids could not be accounted for by contamination by either Leydig or Sertoli cells. No proenkephalin mRNA was detectable in extracts of mature sperm. These data suggest that developing germ cells may be a major site of proenkephalin synthesis in the adult testis and that proenkephalin-derived peptides may function as germ cell-associated hormones or autocrine/paracrine factors.